A preliminary study: The sequential use of the risk malignancy index and contrast-enhanced ultrasonography in differential diagnosis of adnexal masses. Issue 29 (July 2018) - Qiu, Li; Yang, Fan; Luo, Hong
Abstract : Abstract: The aim of this study was to explore the sequential use of risk malignancy index (RMI) combined with contrast-enhanced ultrasonography (CEUS) in identification diagnosis of adnexal masses. This study contained 2 steps: first, 151 patients were analyzed retrospectively with RMI 1, RMI 2, and RMI 3 indices; receiver operating characteristic (ROC) curves were plotted to analyze area under the curves (AUC), and then RMI cut-off value was obtained according to maximum Youden index (YI, Sensitivity + Specificity − 1) and calculating diagnostic sensitivity, specificity, positive/negative predictive value, and accuracy. Second, 151 cases were divided into 2 groups randomly (105 in study group and 46 in test group); in the study group, the lower cut-off value (LC), upper cut-off value (UC), CEUS cut-off value according to maximum YI, and then these cut-offs were validated in test group. There was no statistical significance in 3 RMI models ( P = .35), and RMI1 model was established randomly for following study. When the RMI1 cut-off value was 149, the YI was maximal (0.53), and the sensitivity, specificity, positive/negative predictive value, and accuracy were 71.0%, 81.7%, 77.1%, 75.6%, and 76.2%, respectively. The LC was 15 (sensitivity was 98.0%), the UC was 3000 (specificity was 98.0%), and the CEUS cut-off value was 7 (maximal YI was 0.81). In the test group (46 cases), combining RMI1 LC (15) and UC (3000) with CEUS cut-off value (7), the sensitivity, specificity, positive/negative predictive value, and accuracy were up to 85.7%, 92.0%, 90.0%, 88.5%, and 89.1%, respectively. CEUS can help RMI to make a more effective differential diagnosis of the adnexal mass. Further validation by additional multicenter prospective trials is required.